Sustainable Development Goals and India’s Commitment to Gender Justice - JAMEEL, ANAS; Ahmed, Waseem (Society & Sustainability, 2022)
Sustainable Development Goals are a set of seventeen interconnected objectives to achieve a sustainable future for all. They take a holistic and multidimensional approach to development to alter our planet by addressing humanity's many difficulties. It is an essential component of all aspects of inclusive and long-term growth. Women need to have equal rights and opportunities and live without fear of prejudice or violence. Goal five expressly mentions gender equality as one of the SDGs. Discriminatory laws must be changed and legislation enacted to advance equality proactively to achieve the goals. Gender-based violence is a top priority for governments all across the world. India is dedicated to promoting equality for all of its residents. The Indian Constitution's Preamble, Fundamental Rights, and State Policy Directive Principles express a strong commitment to gender equality. Also, India is the signatory of UN Conventions like CEDAW, where its pledge towards gender justice is evident. Furthermore, India has incorporated various domestic laws in pursuance of its responsibility towards Gender Justice. However, in India, Discrimination against women remains a profound issue despite reforms in various laws and different policies. Several concerns like female labor force participation, crimes against women, education among women, and discrimination are evident. This paper mainly throws light on the status of Gender Justice in India. It will help the stakeholders working on SDGs and Gender justice in policy development. It will highlight the gains and gaps that India has so far accomplished and encountered.